ODL webinar series / Norul Fadhilah Ismail and Mahfuzah Mahayadin - Ismail, Norul Fadhilah; Mahayadin, Mahfuzah (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
FSKM KP has organised an ODL Webinar Series on 2-4 September 2020 during FSKM Digital Week. There are five series of ODL Webinar that successfully run during the week namely 1) Google Form: Creating and Grading Online Assessment 2) Microsoft Teams: The Introduction 3) Jamboard: Collaborative Digital Whiteboard with Google Meet 4) Interactive Teaching and Learning using EdPuzzle 5) How to Connect yourDevice to Smart TV using WiFi Dongle? The webinars have been recorded using google meet application and FSKM UiTM Kuala Pilah Facebook Live that takes two hours for each sessions. The objectives of this program are to share the informations and knowledge among staff at UiTM Negeri Sembilan and others in using Google Forms and Google Slides interactively for the purpose of building online questions and to produce an effective teaching aids using Microsoft Teams and EdPuzzle.